Estudio de Prefactibilidad para la Exportación de Aceite de Aguacate de la variedad tipo Hass hacia el Mercado de Países Bajos (2022)
Avocado oil is a product of vegetable origin that has become in recent years a favorite of consumers when cooking, due to the source of nutrients, vitamins, and health benefits it provides. Considering the purpose of this business plan, it is necessary to develop a process route to determine the feasibility of exporting Hass avocado oil from the city of Ibagué to the Netherlands. To carry out the above described, it is necessary to take as a reference the statistics of trend and global consumption of the product, besides reviewing market and competition issues, determine an operative plan that is in accordance with the due logistic process and a financial plan, which from this will lead to a good development of the project. Therefore, it has been possible to identify the feasibility of exporting this business plan to the Dutch market following the parameters.